2017
DOI: 10.1155/2017/4863431
|View full text |Cite
|
Sign up to set email alerts
|

The Dual Burden of Malnutrition and Associated Dietary and Lifestyle Habits among Lebanese School Age Children Living in Orphanages in North Lebanon

Abstract: Childhood is a crucial period affecting physical and intellectual development. Although children living in orphanages are among the most vulnerable groups at risk of malnutrition, there is scarcity of data concerning their nutritional status in Lebanon. To investigate these data, a cross-sectional survey was conducted including a sample of 153 institutionalized children aged 5–14 years from all orphanages in Tripoli. Nutritional status was assessed using anthropometric, clinical, and dietary tools. Interpretat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Boys, compared to girls, spent almost twice as much time on physical activity. Kassas & Ziade (2017) Compared to the Dietary Guidelines for American Children and Adolescents 2015 and based on a semiquantitative food frequency questionnaire, more than half were estimated to have inadequate daily intake of vegetables, fruit, and proteins compared to the recommendation. 94.8% consumed three meals per day.…”
Section: Discussionmentioning
confidence: 99%
“…Boys, compared to girls, spent almost twice as much time on physical activity. Kassas & Ziade (2017) Compared to the Dietary Guidelines for American Children and Adolescents 2015 and based on a semiquantitative food frequency questionnaire, more than half were estimated to have inadequate daily intake of vegetables, fruit, and proteins compared to the recommendation. 94.8% consumed three meals per day.…”
Section: Discussionmentioning
confidence: 99%
“…Data were collected by face to face interview using a pre-tested structured questionnaire adapted from previous studies. 6 , 23 - 25 The questionnaire was administered using local languages—either Afaan Oromoo or Amharic. Data on sociodemographic characteristics, diet, and related information were collected from their care givers and the orphan center directors.…”
Section: Methodsmentioning
confidence: 99%
“…Although the Lebanese guidelines specifically target the adult population, a need exists for greater attention to dietary guidelines in the paediatric population as well. A study of orphaned children in Tripoli showed a high prevalence of sedentary behaviour and inadequate intakes of vegetables, fruits and proteins, as well as high intakes of sweet and salty snacks, compared with the American dietary guidelines ( 41 ) . Promotion of the traditional Lebanese dietary pattern and the messages of the Lebanese Cedar Food Guide could help to inform policy for the most vulnerable children.…”
Section: The Food-based Dietary Guideline Manual For Promoting Healthmentioning
confidence: 99%